Persepsi Masyarakat dalam Pengelolaan Kawasan Hutan Mangrove sebagai Wilayah Produksi di Kabupaten Luwu - Arfan, Amal; Maru, Rosmini; Side, Syafruddin (UNIVERSITAS NEGERI MAKASSAR, 2020)
Sustainable production forests are forests that can produce products of economic value that can be used for the needs of today's life and the future. The purpose of this study is to analyze people's perceptions in managing mangrove forests as production forests. Data collected in this study are primary data and secondary data. Primary data were collected directly from informants and respondents through direct interviews. Secondary data obtained through citing data from research results, journals, books, reports that have relevance to the research conducted. The population of this research is people aged 20 - 60 years. The sampling technique is carried out using proportional stratified random sampling, which is based on the stratification of the types of activities around the mangrove forest area. The results showed that it was concluded that people's perceptions of products produced by mangrove forests were very beneficial in addition to being a source of income as well as an alternative source of livelihood. In the case of managing mangrove forests as production forests, the community wants a division of management zones such as protected forest zones, conservation forests, production forests and cultivation zones. They also want them to be involved from the planning stage to the conservation / utilization of the economic resources of the mangrove forest.